Biocorrosion of copper by nitrate reducing Pseudomonas aeruginosa with varied headspace volume. (July 2022) - Dou, Wenwen; Pu, Yanan; Gu, Tingyue; Chen, Shougang; Chen, Zhaoyang; Xu, Zixuan
Abstract: Headspace to liquid volumetric ratio can impact bacterial activity, which affects the metabolic process and extracellular electron transportation (EET) of microbial biofilms. In this work, the ratio of headspace volume to culture medium volume was varied to investigate the behavior of Cu microbiologically influenced corrosion (MIC) by P. aeruginosa as a nitrate reducing bacterium (NRB). This NRB produced ammonia as a toxic metabolite that inhibited its growth in anaerobic bottles. The results showed that a larger headspace volume led to lower ammonium concentration in the liquid phase (due to escape of ammonia to the headspace), higher planktonic and sessile cell counts, deeper pits and higher uniform corrosion rate. With a fixed culture medium volume of 200 mL, the weight loss of Cu coupons corresponding to 500 mL and 200 mL headspace volumes were approximately 1.9-fold and 1.5-fold larger than that for 50 mL headspace volume, respectively, with corresponding pit depth increased by 2.6 times and 1.7 times, respectively. Ammonia acted as a complexing agent, not an oxidant (electron acceptor) in the system. The terminal electron acceptor was nitrate. The reduction of nitrate in the cytoplasm of P. aeruginosa using extracellular electrons released by Cu oxidation is thermodynamically favorable. Thus, Cu corrosion by the nitrate reducing P. aeruginosa biofilm belongs to EET-MIC. Highlights: Nitrate reduction coupled with Cu oxidation is thermodynamically favorable. NH4 + in P. aeruginosa broth inhibits sessile cell growth and thus impacts MIC. Increased headspace leads to higher sessile cell count and more severe Cu MIC. Localized corrosion and general corrosion are observed in 14-day tests. Data support the mechanism for Cu MIC with electron uptake by the nitrate reducer.